ANALISIS POSITIONING EXTRA JOSS BERDASARKAN PERSEPSI KONSUMEN MINUMAN ENERGI NON CAIR (Studi Kasus Konsumen Buruh Pabrik Di Kawasan Industri Pulo Gadung) - Rizal Edy Halim; Awan Raharjo (Media Riset Bisnis & Manajemen, 2006)
“Perception is more important than reality” (Al Ries & jack Trout, 2003). This is the sentence that can give us explanalion why companies want to spend plenty of money for advertising and promotion. So do with Extra Joss that spent much money for their promotion. But there are some concepts that have to be done for making the spending usefull One of those concepts is positioning-the act designing of the companies o distinctive place in the mind of target market (Kotler, 2003). The main purpose of this study is to identifying positioning of Extra Joss among ils close competitor based on perception ofits consumer, specifically labor worker on Industrial Estate Pulogadung. There are also trhee major pupose of this study: 1. to identifying brand awareness of non-liquid energy drink, 2. to identifying determinant alribut of non-liquid energy drink, 3. to identifying positioning Extra Joss based on perception of its consumer. The tools of the analysis of this study are correspondence analysis thal can give us a picture of perceptual map where product and those atribut can be plotted together, Factor analysis and analysis of mean score are also used for analysis.